The Effect of Price Perception on Purchase Intention with Attitude as Mediation - Mayori, Welda; Suziana, Suziana; Maruf, Maruf (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This study aims to examine the influence of price perception, and hedonistic lifestyle on purchase intention and attitude towards imitation buttonscarves hijab. Sampling using purposive sampling method, with a sample size of 155 respondents, namely people in Padang City who know information about imitation buttonscarves hijab. Data were collected using questionnaires. Data analysis techniques using SEM through PLS software. The results of the data analysis prove that price perception has a positive and significant effect on purchase intention, price perception has a positive and significant effect on attitude, the attitude has a positive and significant effect on purchase intention, and price perception has a positive and significant effect on purchase intention through attitude.